Shakespeare as a prompter of language awareness: stylistics as a way of reading between/beyond the lines - Lin, Hui-Wei (2005)
This study responds to a double call. Firstly, it aims to develop an empirical and pedagogical perspective on the integration of language and literature teaching. Secondly, it attempts to construct a language awareness (LA) assessment tool to keep pace with developments in reading. To this end, the study investigates the extent to which a stylistic exploration of Shakespeare's language can enhance EFL students' language awareness, which is defined for the present purpose in terms of a number of stylistic devices (e.g. metaphor) which potentially contribute to the 'literariness' of a text.